The Impact of Vocational Education on Economic Growth and Development across the G20 Countries (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
This paper explores the impact of vocational education on economic growth and  development. Vocational education refers to the education and training that prepares individuals for jobs that require specific skills or knowledge. The paper examines theeconomic benefits of vocational education, including job creation, increase in skilled labour, improved productivity, reduction of poverty, and contribution to GDP. The role of vocational education in technology advancement is also explored, as well as case studiesof countries that have successfully implemented vocational education programs. Additionally, the paper discusses the challenges and opportunities for vocational education and provides recommendations for policymakers and stakeholders. The findings suggest that investing in vocational education can have significant positive effects on economic growth and development. Therefore, it is recommended that policymakers and stakeholders prioritize vocational education in their economic development plans and strategies. This paper explores the skills and innovation landscape in G20 countries. The aim is to understand the current state and trends in research and innovation within the G20 context. The paper concludes by providing policy implications for enhancing skills development and fostering innovation in these countries.